EXPLORING EXPERIENCES, CHALLENGES AND COPING STRATEGIES OF SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) PATIENTS - Nur Hanani, Mohd Razman (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study explored the experience of individuals with SLE, identify their challenges and the individual coping strategies including the support system available. Eight SLE patients diagnosed with SLE for two years or more were interviewed using semi-structured interview via telephone call. The findings revealed the challenges which include negative emotional consequences, changes of work and education life, lack of empathy and difficulty of getting pregnant. The Positive Psychology PERMA Model and Self-determination Theory as their coping strategies are discussed. The analysis also revealed that the participants received emotional support, companionship support and informational support from all people. This study could have further implications on the psychological wellbeing of SLE patients, a rare autoimmune disease with common symptoms.